Gangrene as a rare manifestation of systemic lupus erythematosus - Arun Kumar Alagesan; R., Kannan; V., Vikrannth; J., Raghav (International Journal of Advances in Medicine, 2023)
Systemic lupus erythematosus (SLE) is a chronic, multifaceted autoimmune inflammatory disease that can affect any part of the body. Peripheral gangrene is a rare manifestation of SLE. We describe a case of 26-year-old female who presented with complaints of bilateral lower limb rash, blackish discoloration of skin over right little finger and right third toe for past 2 months. On evaluation her anti RNP, anti SM and anti dsDNA antibodies were strongly positive. She was treated with IV unfractionated heparin, IV corticosteroids, IV antibiotics and other supportive measures.